A Multilevel, Agent-Centered Analysis of Intersectionality in a Hispanic-Serving Institution: The Case of College Internship Access for Latinx Students - Matthew T. Hora; Matthew Wolfgram; Adrian H. Huerta; Changhee Lee; Anita Gopal (SAGE Publishing, 2022)
Internships are widely viewed as "door openers" to opportunity, yet students without ample financial, social, and institutional supports are often excluded from these experiences. This exclusion is especially problematic for Latinx students attending Hispanic-Serving Institutions, for whom an internship could be transformative. In this article, we elaborate upon Núñez's (2014) multilevel model of intersectionality to highlight how agents' perceptions, social categories, embodied practices, and broader contextual forces interrelate to shape Latinx students' access to internship opportunities at a university in the border region of Texas. Using inductive thematic, correlational, and social-network analysis techniques to analyze survey (n = 192) and focus group (n = 12) data, we find that gender, academic major, socioeconomic status, and race intersect with organizational (e.g., insufficient information) and contextual (e.g., labor markets) factors to shape students' access and perceptions. We provide recommendations for disrupting systemic inequalities in internship access and culturally appropriate programming and ideas for future research.